2012
DOI: 10.1007/s12610-012-0189-9
|View full text |Cite
|
Sign up to set email alerts
|

Carcinome urothélial de l’urètre: une nouvelle observation et revue de la littérature

Abstract: Résumé Le carcinome urothélial de l’urètre masculin est une tumeur exceptionnelle. Nous rapportons une nouvelle observation de carcinome urothélial de l’urètre chez un homme de 64 ans qui avait consulté pour une dysurie. L’urétrocystographie rétrograde et mictionnelle (UCRM) réalisée avait mis en évidence des images de rétrécissement de l’urètre bulbopénien traité par urétroplastie. L’examen histologique de la pièce d’urétrectomie a révélé un carcinome urothélial de l’urètre. Le patient refusa tout t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…In 2012, Gowe et al in Ivory Coast reported a case of metastatic PUC (T3N3M1) who was offered emasculation and systemic chemotherapy. The patient refused care and died within 6 months [ 33 ]. Though the disease may be rare, it is also apparent that the few cases that may erupt are either left undiagnosed due to diagnostic challenges, poor health seeking behaviors of patients or lack of access to specialized care.…”
Section: Discussionmentioning
confidence: 99%
“…In 2012, Gowe et al in Ivory Coast reported a case of metastatic PUC (T3N3M1) who was offered emasculation and systemic chemotherapy. The patient refused care and died within 6 months [ 33 ]. Though the disease may be rare, it is also apparent that the few cases that may erupt are either left undiagnosed due to diagnostic challenges, poor health seeking behaviors of patients or lack of access to specialized care.…”
Section: Discussionmentioning
confidence: 99%